Is digit ratio (2D:4D) associated with the choice for the uniformed versus a civil study course by the Polish youth? - Kociuba, Marek; Chakraborty, Raja; Ignasiak, Zofia; Kozieł, Sławomir (Anthropological Review, 2019)
The 2nd to 4th digit ratio (2D:4D) is a sexually dimorphic trait determined by the relative balance of prenatal testosterone (T) and oestrogen during the intrauterine development of foetus. Males on average have relatively lower 2D:4D than women in population. Lower 2D:4D is very often linked with greater physical ability, strength, superior sporting performance and many personality traits and behaviours which are seen more among the males. Recently, lower 2D:4D were associated with military and police services among the Polish women. The objectives of this study were to examine whether 2D:4D differed between the students of a study course for future military service and a civil study course and whether sex difference in this ratio is present in both these groups. The cross sectional study included 50 boys and 42 girls enrolled in the uniformed course and other 56 boys and 50 girls of a general course in an upper-secondary School. The lengths of the second (2D) and fourth fingers (4D) of each hand were measured to have the 2D:4D ratio. Height and weight were also recorded. Overall, as well as among the civil course students, males showed significantly lower mean 2D:4D compared to the females. But there was no significant sex difference in digit ratio among the uniformed course students. Besides, the females under uniformed course showed lower 2D:4D than the females in civil course, whereas, the male uniformed students had similar or almost same 2D:4D values with the male civil course students. Increased prenatal testosterone exposure might have a role in determining the choice towards a challenging future occupation and such effect is perhaps more pronounced in women than in males.